2016
DOI: 10.1161/circresaha.116.308034
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Influence on Metabolism and Inflammation in Atherosclerosis

Abstract: Many aspects of human health and disease display daily rhythmicity. The brain’s suprachiasmic nucleus, which interprets recurring external stimuli, and autonomous molecular networks in peripheral cells together set our biological circadian clock. Disrupted or misaligned circadian rhythms promote multiple pathologies including chronic inflammatory and metabolic diseases like atherosclerosis. Here, we discuss studies suggesting that circadian fluctuations in the vessel wall and in the circulation contribute to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
139
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(142 citation statements)
references
References 179 publications
(207 reference statements)
3
139
0
Order By: Relevance
“…Circadian rhythm is a fundamental biological system in humans, animals and plants that regulates various physiological functions such as sleep–wake cycle, energy metabolism, cell division, post-transcriptional regulation (Koike et al, 2012; Cardinal-Aucoin and Steel, 2016; Lopez-Minguez et al, 2016; McAlpine and Swirski, 2016; Nitschke et al, 2016), and endocrine system (Gachon et al, 2004; Lowrey and Takahashi, 2004). The master circadian clock, located in the suprachiasmatic nucleus (SCN), is an essential activator of downstream molecular events critical to the generation of circadian rhythms (Dunlap, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Circadian rhythm is a fundamental biological system in humans, animals and plants that regulates various physiological functions such as sleep–wake cycle, energy metabolism, cell division, post-transcriptional regulation (Koike et al, 2012; Cardinal-Aucoin and Steel, 2016; Lopez-Minguez et al, 2016; McAlpine and Swirski, 2016; Nitschke et al, 2016), and endocrine system (Gachon et al, 2004; Lowrey and Takahashi, 2004). The master circadian clock, located in the suprachiasmatic nucleus (SCN), is an essential activator of downstream molecular events critical to the generation of circadian rhythms (Dunlap, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous studies, we found a significant increase of plasma lipid levels in JL mice supporting the link between CRD and cardiovascular diseases. [44][45][46] Besides lipid metabolism, feeding-signalling and insulin-glucose axis are also under circadian regulation. Several studies reported elevated leptin and insulin resistance in CRD associated with weight gain, obesity and type-2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It was well known that vascular endothelial injury in the susceptible location for atherosclerosis in vessels was the prerequisite for AS formation, while the atherosclerotic plaque was the consequence of subsequent vascular repair reaction induced by shear stress [37][38][39]. Thus, dysfunctional endothelium in the atherosclerosis-susceptible location is an early manifestation of atherosclerosis [40].…”
Section: Dual Effects Of Shear Stress On Atherosclerosismentioning
confidence: 99%